Collective efficacy based on the coaching efficacy in female profesional basketball teams - Rad, L. S.; Gharehgozli, S. (European Journal of Experimental Biology, 2013)
The purpose of the present research was to determine the relationship between coaching efficacy and collective efficacy in professional womens basketball teams. 12 teams consisting of 12 head coaches (41.41±8.82yrs. age; 18.25±7.47 yrs. coaching experience) and 116 players (23.74±4.36 yrs. age; 9.74±4.01 yrs. athletic experience; 4.32±2.96 yrs. professional experience) were randomly selected from the teams in Iran's professionalbasketball leagues in 2011. Coaching Efficacy Scale (CES; Feltz et al. 1999) and Collective Efficacy Questionnaire for Sports (CEQS; Short et al., 2005) were used along with a demographics questionnaire for collecting data. Pearson correlation coefficient and a multivariate regression model were used for data analysis. The results showed that, among the dimensions of coaching efficacy, character building is negatively associated with effort, persistence, unity, and overall level of efficacy (p < 0.05), while no other significant relationship was observed between other variables. Regression analysis indicated that among the dimensions of coaching efficacy (R2 = 0.122; p = 0.006; F(4,111) = 3.845), motivation (p = 0.041;ß = 0.655) and character building (p = 0.019;ß= -0.617) were the most important predictors of efficacy in professional womens basketball teams. The present findings support the conceptual model of coaching efficacy developed by Feltz et al. (1999) regarding the positive effect of motivation on collective efficacy and highlight the necessity to review and expand this model.